2014
DOI: 10.3851/imp2961
|View full text |Cite
|
Sign up to set email alerts
|

Raltegravir plus Two Nucleoside Analogues as Combination Antiretroviral Therapy in HIV-Infected Patients who Require Cancer Chemotherapy

Abstract: Our results show that a RAL-based regimen is safe and effective in patients requiring chemotherapy, irrespective of type and of duration of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In theory, integrase inhibitors (IIs) are eligible while these agents do not interfere with the CYP enzyme system and therefore no alternations in pharmacokinetics and exposure to toxic metabolites are expected. This approach has recently been suggested by a German as well as by an American HIV-treatment group and is supported by a report on a small cohort of Spanish HIV-positive patients undergoing safe and effective chemotherapy while on raltegravir based cART [ 26 28 ]. A prospective study of the use of II’s versus NNRTI`s or PI`s is highly recommended.…”
Section: Discussionmentioning
confidence: 93%
“…In theory, integrase inhibitors (IIs) are eligible while these agents do not interfere with the CYP enzyme system and therefore no alternations in pharmacokinetics and exposure to toxic metabolites are expected. This approach has recently been suggested by a German as well as by an American HIV-treatment group and is supported by a report on a small cohort of Spanish HIV-positive patients undergoing safe and effective chemotherapy while on raltegravir based cART [ 26 28 ]. A prospective study of the use of II’s versus NNRTI`s or PI`s is highly recommended.…”
Section: Discussionmentioning
confidence: 93%
“…This can lead to increased toxicity and a potential delay in chemotherapy treatments. In this setting, non-boosted integrase inhibitors are increasingly being used due to a more favorable drug-drug interaction profile and better tolerability [23,24], as observed in our cohort. Although this may have impact on the In this study, patients with HIV and cancer experienced higher mortality than those without HIV.…”
Section: Discussionmentioning
confidence: 58%
“…35,36 One observational cohort study of 30 patients who initiated or were changed to a raltegravir-based ART as a result of a cancer diagnosis showed a mean increase in CD4 count of 49 cells/mL; only 1 discontinuation as a result of virological failure, which was attributed to nonadherence; and no additive adverse effects attributed to ART. 35 A retrospective study in 154 patients that compared various HIV regimens showed that INSTI-based treatment was 9 times (95% CI = 1.4-50.8) more likely to be effective, as shown by HIV RNA <200 copies/mL at 6 months, than PI-based treatment. 36 Adverse effects related to ART occurred in 35% (17/49) of patients receiving PIs and 3% (1/30) of patients receiving INSTIs.…”
Section: Initiation/continuation Of Artmentioning
confidence: 99%